Erratum: LNGAT: Local neighborhood graph attention network (Journal of Electronic Imaging (2022) 31:5 (053034) DOI: 10.1117/1.JEI.31.5.053034) - Sun, Yukuan; Ma, Haoran; Ko, Young Bae; Wang, Jianming (Journal of Electronic Imaging, 2022)
This article [J. of Electronic Imaging, 31(5), 053034 (2022) https://doi.org/10.1117/1.JEI.31.5 .053034] was originally published on 27 October 2022 with an error in one of the authors’ names. Young-Bae Ko, of the AJOU University, Suwon, Republic of Korea, was listed as “Young-Bae Bo” in the author list of the pdf and the author biography in both the online paper and the pdf.